iPad in primary school: the role of teachers’ attitudes towards using the tablet in classroom - Dovigo, Fabio (Formazione & insegnamento, 2017)
School attention towards the rapid spread of new technologies as a means to improve the learning experience of pupils have steadily grown over time. Many researchers suggest that tablets are an especially versatile technology in education. They introduce students to a mobile form of learning and allow them gather and manage real-time data from the large amount of information they face today. The iPad is one of the most used tablet in schools, currently covering over 75% of the global education market. However, despite the obvious potential of iPad for learning, investigation addressed to confirm the actual benefits of using it, especially in primary school, are still limited. From this point of view, special attention should be paid to the role of teachers’ attitudes, ie whether they are actually inclined to integrate this device into their daily teaching practices, and the reasons why they would decide whether or not to do so. Our research is directed to deepen what are the attitudes of primary school teachers face to the introduction of the iPad in their teaching activities, and what are the positive and negative aspects they came upon using the tablet in classroom.